Pengaruh Customer Need, Cost, Convenience Dan Communication Terhadap Keputusan Penggunaan Jasa Transportasi Maxim Di Kota Bandung - Yanti, Sumi; Fadilla, Arif (Jurnal Ilmiah Wahana Pendidikan, 2024)
This study aims to analyze the effect of customer need, cost, convenience, and communication on the decision to use Maxim transportation services in the city of Bandung by using quantitative methods and verification descriptive analysis. Sampling used the Nonprobability Sampling method with purposive sampling which resulted in a total sample of 365 respondents. The analysis technique used is multiple linear regression analysis and hypothesis testing using the t test and f test using the SPSS 29 tool. The results show that there is a partial influence between customer need, convenience and communication on usage decisions but cost does not partially affect the decision use. Meanwhile, simultaneously, all variables have an influence on the decision to use Maxim in the city of Bandung.